PERAN PENDIDIKAN DAN PELATIHAN TERHADAP KUALITAS LAPORAN KEUANGAN DESA DI KECAMATAN MANGARABOMBANG KABUPATEN TAKALAR - REZKYAWAN, REZKYAWAN; Lubis, Bastian; S, Suhendra (Patria Artha Management Journal, 2024)
This research was conducted in Mangarabombang District, Takalar Regency with the aim of finding out the role of education and training for village financial statements based on Government Regulation Number 71 of 2010 concerning Government Accounting Standards.This study shows that education and training play an important role in the understanding and management of village financial statements. Informants with Master's and Bachelor's education backgrounds have an easier time understanding village financial statements, while those with a high school education background have difficulties. The training has been proven to improve the ability of Village Heads, Village Secretaries, and Heads of Financial Affairs to prepare reports, manage finances, and use systems such as the Village Financial System (SISKEUDES), which plays a role in maintaining transparency and stability of village finances.